Arthur Machen: A Novelist of Ecstasy and Sin : With Two Uncollected Poems by Arthur Machen - Starrett, Vincent, 1886-1974; Machen, Arthur, 1863-1947 (Salt Lake City, UT : Project Gutenberg, 2011)
"Arthur Machen: A Novelist of Ecstasy and Sin" by Vincent Starrett is a critical biography written in the early 20th century, specifically during the post-World War I era. The book examines the life and works of Arthur Machen, a Welsh author renowned for his exploration of themes such as mysticism, ecstasy, and the duality of sin. Starrett seeks to shed light on Machen$1 (Bs importance as a literary figure and to challenge the neglect he faced from contemporary critics who overlooked his profound contributions to fiction, especially in the realm of horror and psychological exploration. In this work, Starrett delves into Machen's literary oeuvre, highlighting key stories and novels that exemplify his unique style and philosophical inquiries. He discusses Machen's major works, such as "The House of Souls" and "The Hill of Dreams," illustrating how they navigate the nuances of ecstasy and sin through rich, evocative prose. Machen's narratives often tread the delicate line between reality and the surreal, featuring vivid imagery and a haunting atmosphere that explore the hidden depths of human experience. Starrett positions Machen as a masterful novelist who grapples with profound questions of existence, morality, and the mystical elements of life that transcend the mundane, ultimately advocating for a reevaluation of Machen's literary significance. (This is an automatically generated summary.)s
Release date is 2011-03-07
E-text prepared by Marc D'Hooghe (http://www.freeliterature.org) from page images generously made available by Internet Archive (http://www.archive.org)
Keywords: Poetry; Machen, Arthur, 1863-1947